Training of cooperative values as a decisive element in new jobs to be created by 21st century cooperatives - Eba Gaminde Egia; Gonzalo Martínez Etxeberria (Boletín de la Asociación Internacional de Derecho Cooperativo, 2019)
Some principles and values exist in cooperative organisations and enterprises that constitute distinguishing aspects. However, the complex situation in which modern cooperative trading companies operate tends to doubt about the adherence to cooperative principles, and may play down the cooperative values. Consequently, this can lead to what it really means for a cooperative to become distorted. Education, training and information are absolutely necessary to avoid that not wanted result. The training of those who want to join cooperatives must be done with an increase in cooperative education for the rest of society in which cooperatives act.